Postcolonial Betrayal? Mysticism and the Past in Nicole Brossard’s Hier and Diane Schoemperlen’s Our Lady of the Lost and Found - Marie Vautier (Canada and Beyond, 2013)
Nicole Brossard’s Hier and Diane Schoemperlen’s Our Lady of the Lost and Found were published in 2001. Both novels explore contemporary “turns” in the humanities—turns that can be seen as a betrayal of the secular worldview and the focus on the New World that dominated our literary concerns of the late twentieth century. Brossard’s text “betrays” contemporary literary and cultural considerations in its foregrounding of accumulated Old World knowledge and religious art. In Hier, Brossard makes multiple references to two religious figures of Catholicism: Marie Guyart—Marie de l’Incarnation, the founder of the Ursuline order in Québec—and the Virgin Mary. In this novel, Brossard is beginning to explore the idea of looking to those women associated with the mystical world, knowledge of whom is buried in our collective memories, in order to turn to mysticism as a way of accessing that “high” provided by metaphysical experiences. Diane Schoemperlen’s novel, Our Lady of the Lost and Found (Our Lady), reveals a number of similar preoccupations to those found in Brossard’s Hier. In Our Lady, a narrator/writer, is “visited” by the Virgin Mary near the beginning of the novel, and the text then alternates between credible domestic scenes and stories of other Marian apparitions, most of which, as Schoemperlen assures us in an afterword, are “based on actual documented accounts” (Our Lady 339). Our Lady contains many reflective passages: comments on historiography; philosophy; and reflections on the nature of story, truth, science and history. The didactic impulse is very strong in both novels, and the urge to teach is centered on works of religious art from Old World civilizations. Faced with the turmoil of the contemporary world, the narrator of Our Lady explores that other world: the world of miracles, Marian apparitions and the thin place to which the act of writing takes one. In this article, Marie Vautier explores how these two 2001 novels highlight mystical women of the religious past, in their discussion of art, culture, the Old World versus the New World, and the limits of the contemporary worldview in a (re)turn to mysticism and summa plus ultra experiences.